A Nose for Justice : A Novel - Brown, Rita Mae (New York : Ballantine Books, 2010)
On Jeep Reed's Wings Ranch near Reno, Jeep, her great-niece, former Wall Street banker Magdalene "Mags" Rogers, and their two dogs King and Baxter investigate a pump company employee's disappearance, along with an environmentalist's shooting "suicide" and the identity of a really cold corpse.
Keywords: Country life -- Fiction -- Nevada; Corporations -- Fiction -- Corrupt practices; Real estate developers -- Fiction; Murder -- Fiction -- Investigation; Dogs -- Fiction; Nevada -- Fiction; Fiction